Sustentabilidade e o turismo cultural religioso na apa pé do morro. - Silva, Vanessa Gomes da (Universidade Federal do Tocantins, 2023)
The main objective of this study is the preliminary analysis of the sustainability pathways in the religious cultural tourism Pé do Morro Environmental Preservation Area, Aragominas (TO), and for this the specific objectives were dedicated to identifying the cultural elements that make up the tourist attractiveness of APA and identify the determining factors for the cultural sustainability of this conservation unit. This work utilized the qualitative methods of data collection and analysis, through bibliographic research and field research. And it was possible to observe that the history of the local community is the factor of greater attractiveness and its relation of belonging has influenced to the tourist development of the region. However, sustainability in all its dimensions has been threatened by the Conservation Unit and, consequently, the future of the community.